A Comparison Between Shear Capacities of Two Composite Shear Walls: DSCSWs and CSPSWs. Issue 2 (3rd April 2019) - Labibzadeh, Mojtaba; Hamidi, Reza
ABSTRACT: In this study, it was attempted to investigate the efficiency of a new type of composite shear walls named as Double Skin profiled Composite Shear walls (DSCSWs) in practice. To this end, 22 Finite Elements (FE) models of DSCSWs with practical geometries have been modeled using ABAQUS/CAE/Explicit v.6.14. These models were developed based on an enhanced verified reference FE model of a laboratory-scale DSCSW model. Obtained shear capacities of these models were compared with equivalent another type of composite shear walls named as Composite Steel Plate Shear Walls (CSPSWs). Results of comparison revealed that DSCSWs with the same concrete panel and steel plate thicknesses used in CSPSWs, but without the reinforcement of the concrete panel and with many lower numbers of intermediate fasteners than that of CSPSWs, provide greater shear capacity than CSPSWs which demonstrates the distinct advantage of DSCSWs.